Different Solution Strategies for Solving Epidemic Model in Imprecise Environment. (13th May 2018) - Mahata, Animesh; Mondal, Sankar Prasad; Ahmadian, Ali; Ismail, Fudiah; Alam, Shariful; Salahshour, Soheil
Abstract : We study the different solution strategy for solving epidemic model in different imprecise environment, that is, a Susceptible-Infected-Susceptible (SIS) model in imprecise environment. The imprecise parameter is also taken as fuzzy and interval environment. Three different solution procedures for solving governing fuzzy differential equation, that is, fuzzy differential inclusion method, extension principle method, and fuzzy derivative approaches, are considered. The interval differential equation is also solved. The numerical results are discussed for all approaches in different imprecise environment.